Management of Esophageal Foreign Body - Haryanto Rahardjo; Ari Fahrial Syam; Marcellus Simadibrata K (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
Foreign body ingestion is a common clinical problem. Objects such as coin, safety pin, meat bolus, bone, denture, etc. are often ingested. They lodge in certain part of esophagus, which may be asymptomatic or develop some symptoms of esophagus or respiratory tract. Plain radiography is indicated for every patient with a known or suspected foreign body. It may appear as radiopaque or radiolucent images. A number of methods can be used to remove esophageal foreign bodies, including: observation, endoscopy, rigid esophagoscopy, Foley catheter extraction, bougienage and sometimes administration of LES relaxant or surgery. Application of those strategies is selected based on the type and location of foreign bodies. Five cases had been managed by different strategies, i.e. two cases were successfully managed by endoscopy; a case was managed through careful observation; another case was managed by pushing object into stomach using endoscopic approach; and the other case was fail when it was managed by Foley catheter but then it was successfully managed by rigid esophagoscopy at ENT Department. All of cases had been managed without any complication. Keywords: esophageal foreign body, foreign body ingestion, procedure removal